A Call to Strengthen Instructional Leadership to Support Learner Achievement During and Post COVID-19: A Systematic Literature Review Approach - Nwosu, Lilian Ifunanya; Matashu, Martha; Buabeng, Assan Thomas (International Journal of Learning, Teaching and Educational Research, 2022)
The coronavirus disease 19 has dismantled the traditional approaches to school management of education, prompting an urgent need to maintain teaching and learning during and post the pandemic. This study thus calls for strengthening instructional leadership to improve learner performance during and post the pandemic. Instructional leadership is an emerging concept from education leadership; however, the literature on educational leadership functions is still in its infancy. Subsequently, there is a lack of a complete understanding of the role of the School Management Team and educators’ instructional practices in managing teaching and learning in education literature. Although the School Management Team should identify and improve instructional practices to help learners attain learning outcomes, this goal is hindered by a lack of compressive insight into the relationship between instructional leadership and learner achievement. The purpose of this Systematic Literature Review is to examine the instructional leadership roles of SMTs and educators as identified by academics and practitioners. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis reporting guidelines were adopted in the study. An electronic search identified 127 publications. After duplication, titles and abstracts were screened, and inclusion and exclusion criteria were considered; 27 full-text version publications were assessed. Findings revealed a comprehensive conceptual relationship between instructional leadership roles at different hierarchical levels and their influence on learner performance. This study contributes a synthesised literature review on strengthening instructional leadership to promote learner attainment. These findings have implications for policymakers interested in promoting learner performance through strengthened instructional leadership during and post the coronavirus. https://doi.org/10.26803/ijlter.21.7.12